Therapeutic Listening as a health intervention strategy: an integrative review - Ana Cláudia Mesquita; Emilia Campos de Carvalho (SciELO, 2014)
Objective To investigate and evaluate the available evidence in the literature regarding the use of Therapeutic Listening as a health intervention strategy. Method Integrative review conducted on the following databases PubMed, CINAHL, The Cochrane Library, EMBASE, LILACS and APA PsycNET without restrictions of year or type of study. The keywords were combined in different ways to ensure extensive search of primary studies. Results Among the 15 studies on Therapeutic Listening, 33% addressed the effect of training on listening skills, 27% focused on the efficacy of listening as an intervention, 20% explored the experiences lived by the subjects regarding listening and 20% discussed various aspects of listening. Conclusion Most studies have strong to moderate level of evidence, although addressing different aspects related to Therapeutic Listening, they have in common the need for recognition of skills on the part of health professionals, to develop an effective process of listening.